Risk Factors and the Role of the Albumin-to-Globulin Ratio in Predicting Recurrence Among Patients with Idiopathic Granulomatous Mastitis - Ciftci AB; Bük F; Yemez K; Polat S; Yazıcıoğlu M (Dove Medical Press, 2022)
Ahmet Burak Ciftci,1 Ömer Faruk Bük,1 Kürşat Yemez,1 Süleyman Polat,1 İrem Melike Yazıcıoğlu2 1Department of General Surgery, Samsun University, Samsun Training and Research Hospital, Samsun, Turkey; 2Department of Pathology, Samsun University, Samsun Training and Research Hospital, Samsun, TurkeyCorrespondence: Ahmet Burak Ciftci, Department of General Surgery, Samsun University, Samsun Training and Research Hospital, Barış Bulvarı, Kadıköy Mahallesi, No: 199 PK:55090 ilkadım, Samsun, Turkey, Tel +90 530 527 7302, Fax +90 362 277 8865, Email aburak.ciftci@samsun.edu.trBackground: Idiopathic granulomatous mastitis (IGM) is a rare inflammatory disease of the breast with a high recurrence rate. The serum albumin to globulin ratio (AGR) is a relatively novel biomarker in inflammatory diseases, and one whose role in the recurrence of IGM remains unknown. This study primarily investigated the potential risk factors for IGM recurrence and whether AGR can be used as a predictive factor.Methods: Patients diagnosed with IGM from pathology reports between 2016 and 2021 were enrolled in the study, and their medical records were analyzed retrospectively. The patients were divided into two groups - recurrence and non-recurrence. Clinical, demographic characteristics, and laboratory parameters were compared.Results: Eighty-five patients were included in the study, recurrence being detected in 16 (18.8%) of these, with a median follow-up time of 39.99± 18.93 months. No relationship was determined between childbearing, breastfeeding, disease severity, or therapeutic approaches and IGM recurrence. While AGR was significantly lower in the recurrence group (p < 0.001), neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) results were comparable in the two groups (p = 0.472 and p = 0.421, respectively). Multivariate analysis identified low AGR (odds ratio (OR): 50.7, 95% CI 5.93- 434.1 P < 0.001) and smoking (OR: 4.45, 95% CI 1.04- 18.9 P = 0.044) as independent risk factors for IGM recurrence.Conclusion: The study findings indicated that AGR at a cut-off value of ≤ 1.179 at diagnosis and smoking exhibited a remarkable performance in predicting the recurrence of IGM. Developing new risk stratification systems for IGM recurrences and using AGR in these classifications may increase the success of treatment.Trial Registration: This study was registered with ClinicalTrials.gov, NCT05409586.Keywords: idiopathic granulomatous mastitis, recurrence, albumin-to-globulin ratio, risk factors